IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING PADA PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR DI SD : PENELITIAN TINDAKAN KELAS - Wardani, Ardita; Nuralida, Dica Asri; Sari, Alisya Widia; Purnamasari, Ratih; Sumayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the diversity of students' social and cultural backgrounds in the learning process. Diversity or difference is not a barrier to learning; instead, it is an important element that can be utilized by teachers as a learning resource to create an inclusive learning environment. The purpose of this research is to improve student learning outcomes in the subject of Pancasila Education through the Culturally Responsive Teaching (CRT) approach. The method used is Classroom Action Research (CAR) conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The research subjects were fourth-grade students at SDN Panaragan 1, Bogor City. The results of the study show an increase in learning outcomes from the pre-action stage (36.3% of students achieving mastery), to the first cycle (71.43% achieving mastery), and the second cycle (92.86% achieving mastery).The implementation of CRT was carried out by integrating local culture into the learning process through regional songs, traditional games, and interactive digital-based media. The conclusion is that the CRT approach can improve students' learning outcomes by creating more inclusive and meaningful learning experiences. Furthermore, the implementation of CRT in this study reinforces the finding that culture-based teaching can help students understand and appreciate their own cultural identity as well as that of others, thereby fostering an inclusive and harmonious learning environment.The implications of this research cover both theoretical and practical aspects. For instance, schools and teachers can enhance educators' skills in applying CRT through training or seminars, which are expected to develop outstanding and professional teachers. This study also opens opportunities for further research, suggesting that CRT can be applied not only in formal schools but also in non-formal educational institutions